Association between the ratio of triglyceride to high-density lipoprotein cholesterol (TG/HDL-c) and chronic kidney disease risk: a large-scale cross-sectional study in a Chinese population - Liao, Yuheng; Wan, Qijun; Hu, Haofei; Song, Haiying (Frontiers in Medicine, 2025)
ObjectiveThe association between lipid metabolism markers, particularly the TG/HDL-c ratio, and kidney dysfunction has not been thoroughly investigated in Chinese wellness examination cohorts. This study examines the correlation between these parameters and evaluates the role of TG/HDL-c as an independent predictor of CKD.MethodsOur multicenter investigation encompassed data from 33,850 consecutive participants across eight major Chinese metropolitan areas (Shanghai, Guangzhou, Wuhan, Dalian, Zhengzhou, Lanzhou, Luzhou, and Guangxi). To evaluate the relationship between TG/HDL-c ratio and CKD, we employed multiple statistical approaches. The primary analysis utilized binary logistic regression to assess the independent association between these variables. We further characterized the relationship pattern through generalized additive modeling (GAM) with smooth curve fitting, implementing the penalty spline method. The reliability of our findings was validated through comprehensive sensitivity analyses, complemented by stratified subgroup evaluations.ResultsThe average age of the study participants was (57.65 ± 9.28) years, with females accounting for 67.15%. The prevalence of CKD was 15.9%, and the median TG/HDL-C ratio was 1.06 (0.69–1.65). After adjusting for covariates, the results indicated a positive correlation between the TG/HDL-C ratio and CKD (OR = 1.17, 95% CI: 1.13, 1.21). There was also a nonlinear relationship between the TG/HDL-C ratio and CKD, with an inflection point at 1.086. The effect sizes on either side of the inflection point were 1.800 (1.542, 2.100) and 1.049 (1.049, 1.411), respectively. Sensitivity analysis confirmed the robustness of the study findings.ConclusionThis study demonstrates a positive and non-linear relationship between TG/HDL-c ratio and CKD in the Chinese health check-up population. TG/HDL-c ratio is strongly related to CKD when TG/HDL-c ratio is more than 1.086. It makes sense to reduce the TG/HDL-c ratio level below the inflection point from a treatment perspective.